Inactivation of folylpolyglutamate synthetase Met7 results in genome instability driven by an increased dUTP/dTTP ratio. Issue 1 (24th October 2019) - Schmidt, Tobias T; Sharma, Sushma; Reyes, Gloria X; Kolodziejczak, Anna; Wagner, Tina; Luke, Brian; Hofer, Anders; Chabes, Andrei; Hombauer, Hans
Abstract: The accumulation of mutations is frequently associated with alterations in gene function leading to the onset of diseases, including cancer. Aiming to find novel genes that contribute to the stability of the genome, we screened the Saccharomyces cerevisiae deletion collection for increased mutator phenotypes. Among the identified genes, we discovered MET7, which encodes folylpolyglutamate synthetase (FPGS), an enzyme that facilitates several folate-dependent reactions including the synthesis of purines, thymidylate (dTMP) and DNA methylation. Here, we found that Met7-deficient strains show elevated mutation rates, but also increased levels of endogenous DNA damage resulting in gross chromosomal rearrangements (GCRs). Quantification of deoxyribonucleotide (dNTP) pools in cell extracts from met7Δ mutant revealed reductions in dTTP and dGTP that cause a constitutively active DNA damage checkpoint. In addition, we found that the absence of Met7 leads to dUTP accumulation, at levels that allowed its detection in yeast extracts for the first time. Consequently, a high dUTP/dTTP ratio promotes uracil incorporation into DNA, followed by futile repair cycles that compromise both mitochondrial and nuclear DNA integrity. In summary, this work highlights the importance of folate polyglutamylation in the maintenance of nucleotide homeostasis and genome stability.